Music and Crossing Bridges - Jurková, Zuzana (Lidé města, 2015)
While the last issue of Urban People devoted to ethnomusicology, entitled Theory and Method in Urban Ethnomusicology (2/2012), had a rather narrow focus, this time we have taken a wider stance. Our aim, through the theme of Crossing Bridges: Journeys, Migrations, and Diaspora, is to find out more about the role music plays in human interactions across geopolitical, social and cultural borders.